Optimized feature selection and zero-parameter channel attention BiLSTM for RPL-attack classification in IoT networks - Sudha Rani Unnam; Kareemulla Shaik (PLoS ONE, 2026)
The increasing adoption of Internet of Things (IoT) devices introduces significant security challenges, particularly in networks based on the Routing Protocol for Low-Power and Lossy Networks (RPL), where resource constraints limit the effectiveness of conventional security solutions. This work presents an optimized deep learning framework for detecting and classifying RPL-based routing attacks. The framework integrates Chaotic Pied Kingfisher Optimization (Ch-PKO) for feature selection with a Zero-parameter Channel Attention Bidirectional Long Short-Term Memory (ZCAtt-BiLSTM) model for classification. Data preprocessing includes cleaning, one-hot encoding, and Pareto scaling to improve data quality and learning stability. The approach is evaluated on the IoT-RPL dataset, covering Blackhole, Flooding, DODAG Version Number, and Decreased Rank attacks. Experimental results show strong performance, achieving 99.305% accuracy, 98.57% F1-score, 0.61% false discovery rate, and 97.949% MCC. Comparative analysis indicates improved performance over baseline models. However, the evaluation is based on simulated data, and the training process introduces additional computational cost, which may affect real-time deployment.